Reception of Ibn al-Hajib in the Central Maghreb and Its Impact on Scientific Education (Islamic Sciences Journal, 2026)
Ibn al-Hājib left a profound scholarly impact across several disciplines, including jurisprudence, legal theory, creed, Arabic grammar, and Qur’anic readings. This paper examines the contexts of his reception and influence in Algeria, addressing the pedagogical crisis that accompanied the teaching of the Mālikī school, and investigating the reasons behind the diminishing focus on his works and the rise of other texts in their place, such as those of al-Subkī, Khalīl, and the creedal writings of al-Sanūsī.The study employs the descriptive method to analyze the historical contexts, and the analytical method to examine scholarly writings and utilize them in understanding the development of pedagogical practice in Algeria.Our findings indicate the presence of an educational crisis among the scholars of the Central Maghreb and show that they relied on Ibn al-Hājib as an interim solution in scholarly formation until instructional abridgments became the standard in teaching. Critical perspectives toward these pedagogical methods persisted, though they were later revisited and refined with the advent of the modern scientific revival.
Keywords: Ibn al-Hājib, Central Maghreb, Khalīl, abridgments